Community Service Program: Quranic Tutoring Strengthening Children's Morals in Ciputri, Pandeglang, Banten - Dedy Khaerudin; Irma Nurmala Dewi; Mislan Mislan; Lucky Setiawan; Budiharjo Budiharjo; Irfan Muhammad; Ganjar Sidik Gandara (Jurnal Pengabdian Cita Masyarakat, 2026)
The decline of Quranic literacy and moral character among rural children urgently requires innovative interventions beyond rigid formal schooling. This study employed a participatory action research design, deploying university facilitators to implement an edutainment mentoring program for ten primary school students in Ciputri Village, Banten. Quantitative evaluations revealed a 36.5% increase in reading fluency and a 45.0% surge in memory retention. Qualitatively, participatory observations demonstrated that egalitarian role models completely eradicated cognitive fatigue and learning resistance. This organically transformed initial indiscipline into robust moral resilience and voluntary social behavior within the learning ecosystem. These empirical outcomes directly disrupt the contemporary hegemony of technological and institutional interventions. Our findings validate that relational methodologies are vastly superior for rural character development. Ultimately, this highly replicable grassroots framework strategically aligns with Sustainable Development Goal Four, empirically proving that joyful spiritual mentoring actively constructs sustainable social capital alongside inclusive quality education for marginalized communities.